(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Students’ success or failure in adolescent years can affect their well-being, self-esteem, motivation, and perspective. Different factors affect these areas of interest in adolescent development, particularly in surviving with academic rigors. Related to this, the study determined the level of self-efficacy and the extent of factors affecting the self-efficacy of Junior High School who were enrolled in Junior High School of Pagudpud Integrated School, which served as the basis for the formulation of a Learner Developmental Program. The researcher used a descriptive correlational design, had observed total enumeration of the total number of junior high school students of Pagudpud Integrated School. Descriptive and inferential statistics were used to treat the gathered data statistically. The results obtained revealed that the respondents have a capable and effective self-efficacy, with academic self-efficacy being the highest and emotional self-efficacy the lowest. Additionally, the self-efficacy of the respondents was moderately affected by their family, school, and community. Then, the age and grade level of the respondents explain their academic self-efficacy; their sex and grade level explain their social self-efficacy, and their grade level explains their emotional self-efficacy. Finally, the community-related factors predicted the academic and emotional self-efficacies while the family-related factors predicted the academic self-efficacy of the respondents. The findings of the study provide further inputs to the nurture of self-efficacy of adolescents by considering the interplay of the predictors. Moreover, revisiting the contributions of these social institutions, the family, community, and school are further advanced for a more effective and responsive nurture program on the development of adolescents.